The Role of Civic and Pancasila Education Teachers in Enhancing Student Learning Motivation at Primary School - Oktovianus Lumapuy; Titus Gaite; Ode Abdurrachman (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Low learning motivation in Primary Schools in remote areas is often a major obstacle in achieving national education goals, especially in the subject of Pancasila and Citizenship Education (PPKn). This study aims to analyze how PPKn teachers influence the learning motivation of fourth-grade students at Neniari Christian Primary School in Taniwel District, West Seram Regency. This study used a descriptive qualitative method involving the principal and fourth-grade teachers as key informants. Data was collected through interviews, observation, and documentation techniques, then analyzed using an interactive model that includes data reduction, data presentation, and verification. The results indicated that PPKn teachers have optimized their role as motivators through four main strategies: strengthening student self-confidence, implementing a humanistic approach, diversifying strategies and engaging learning media, and providing consistent appreciation. Supporting factors for the effectiveness of teachers' roles include the availability of adequate school facilities and the quality of pedagogically competent human resources. However, this process still faces obstacles in the form of fluctuations in student learning interests and a sometimes-limited variety of learning strategies. This research contributes to providing empirical references regarding motivation-strengthening models in remote areas and serves as an evaluation basis for policymakers in improving the quality of education in areas with significant geographical challenges.